Lipid Metabolism and its Mechanism Triggered by Supercritical CO2 Extract of Adlay (Coix lacryma-jobi var. ma-yuen (Rom. Caill.) Stapf) Bran in High-Fat Diet Induced Hyperlipidemic Hamsters - Huang, Chiao-Chih; Lin, Tzu-Ching; Liu, Chiung-Hui; Hu, Hao-Chun; Yu, Szu-Yin; Wu, Shu-Jing; Yen, Ming-Hong; Tsai, Yi-Hong; Chang, Fang-Rong (Frontiers in Pharmacology, 2021)
Adlay (Coix lacryma-jobi var. ma-yuen (Rom. Caill.) Stapf) seeds are edible crop classified as Traditional Chinese Medicine (TCM). Adlay bran (AB) is one of the wastes generated during adlay refining processes. In this work, supercritical fluid extract of AB (AB-SCF) was investigated to reveal its lipid regulating potential and decode its bifunctional ingredients. AB-SCF×0.5 (30.84 mg/kg/body weight), AB-SCF×1 (61.67 mg/kg/BW), AB-SCF×5 (308.35 mg/kg/BW) and AB-SCF×10 (616.70 mg/kg/ BW) were administrated to high fat-diet (HFD) induced hyperglycemic hamsters for 8 weeks. The results indicates that AB-SCF displays a prevention of dramatic body weight gains, lower levels of serum TG, TC, LDL-C and higher in HDL-C, amelioration of cardiovascular risk, alleviation of hepatic TG, TC and lipid peroxidation, and enhancement on cholesterol metabolism with higher bile acid excretion. Investigations on energy metabolic mechanism demonstrates that the hyperlipidemia mitigating capacities of AB-SCF are up-regulated on lipoprotein lipase, AMPK, p-AMPK and down-regulated at fatty acid synthase. Major bio-functional lipid compositions are identified as linoleic acid (28.59%) and oleic acid (56.95%). Non-lipid chemical and active markers are confirmed as 3-O-(trans-4-feruloyl)-β-sitostanol (1463.42 ppm), 3-O-(cis-4-feruloyl)-β-sitostanol (162.60 ppm), and β-sitosterol (4117.72 ppm). These compositions might synergistically responsible for the mentioned activities and can be regarded as analytical targets in quality control. AB-SCF may be considered as a promising complementary supplement, and developed as a functional food or new botanical drug in the future.